Interpenetrasi Agama Kristen dan Agama Suku dalam Tradisi Cuci Negeri di Hukurila - Agustinus O. Lopuhaa (Institut Teknologi Sepuluh Nopember, 2019)
Abstract This study aims to describe the interpenetration process betweenChristianity and Tribal religion in the Cuci Negeri ritual in Hukurila. Thedescription is based on a strong dialectical process between belief systems tolook for forms and give each other values in community rituals. The beliefsystem and public narratives in interpreting this ritual are living texts, whichmake this study use hermeneutic analysis. From the hermeneutic analysis ofthe text, the Cuci Negeri ritual that experiences an interpenetration processhas given birth to new values in the Hukurila community. The new value thenbecomes a shared value in the belief system of the Hukurila community.